Rekonstruksi Paradigma Studi Islam Pasca Orientalisme Melalui Pendekatan Fenomenologi Richard C. Martin - Muwaffiqillah, Moch. (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This article aims to illustrate how the phenomenological approach developed by Richard C. Martin can be used to strengthen post-Orientalist Islamic studies. In this article, we outline the key concepts in phenomenology according to Richard C. Martin, including intuition, description, and reflection. This article then explains how this approach can be applied to Islamic studies. Using a phenomenological approach, researchers can gain a deeper and more comprehensive understanding of religious experiences in Islam. Furthermore, this article discusses the benefits and implications of phenomenology in Islamic studies. This study uses a qualitative approach with a literature review type of research, which means that data are collected from various existing sources, such as books, journals, articles, and writings related to the study of Islam through phenomenology in the view of Richard C. Martin. The use of a phenomenological approach can help overcome some of the challenges in Islamic studies, such as researchers’ subjectivity and diversity of interpretation. Using this approach, researchers can explore a broader understanding of the diversity of religious experiences in Islam and respect individual perspectives. In conclusion, this article presents the phenomenological approach developed by Richard. Martin could be a useful tool for strengthening Islamic studies. By understanding religious experiences in Islam through a phenomenological lens, researchers can achieve a deeper understanding and encourage dialog and understanding between individual Muslims and non-Muslims inherited by old orientalists.